Sort by

- Relevance
- |Time

This is not an identity. The

**LHS**does not equal the RHS. Try putting t = pi/4 in the**LHS**, and it will not equate with the RHS.1 Answers · Science & Mathematics · 13/04/2010

Let...[1 / 2*square root of X] = K

**LHS**= K / (X-2)....multiply top and bottom by -1 ...= -K / -(X -2) = -K / (2 -X ) = RHS2 Answers · Science & Mathematics · 25/11/2011

...difference between them is less than a certain amount, so if(abs(

**LHS**-RHS)<1e-8) .......... or something like that.1 Answers · Computers & Internet · 20/10/2011

...'s need to be programmed to the vehicle anyway). BTW, the

**LHS**does not use a ballast resistor.6 Answers · Cars & Transportation · 27/06/2007

...scold people for doing it that way). The way to compute it is:

**LHS**=(a*root1+b)*root1 + c that is 4 floating point operations...2 Answers · Computers & Internet · 17/02/2011

... about. As in: √(x - 1) + 1/√(x - 1) = 0 I might say, the

**LHS**simplifies to: x/√(x - 1) Then I might say, so now we...1 Answers · Science & Mathematics · 09/03/2010

Left Hand Side e.g x + 1 >= 7 x + 1 is the

**LHS**P.S: Allen is right4 Answers · Science & Mathematics · 11/11/2010

Intrepid all the way. By the way, how are you doing at college?

7 Answers · Cars & Transportation · 07/12/2006

...cos ^2 x) = (1- cos x)^2/((1-cos x)(1+ cos x)) = (1- cos x)/(1+ cos x) edit: for

**LHS**to be defined sin x cannot be zero( if it is zero ...7 Answers · Science & Mathematics · 12/04/2012